ANALISIS PENGARUH KUALITAS JASA,NILAI YANG DIRASAKAN,CITRA MEREK MELALUI KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN (Studi pada PT. Pos Indonesia(Persero)) - Dwi Putri, Dea Gustiani; Santoso, Suryono Budi (Diponegoro Journal of Management, 2018)
This study aimed to analyze the effects arising from the service quality ,perceived value,and brand image on satisfaction, , its influence on loyalty from PT.Pos Indonesia (Persero). The variables used in this study is service quality ,perceived value, brand imageÂ  as an independent variable, then the satisfaction as an intervening variable lastly, the Loyalty as the dependent variable. The sample in this study were 170 respondents from the consumer of PT.Pos Indonesia (Persero)The method used is non- probability purposive sampling by distributing questionnaires to the respondents (customer). In this study developed a theoretical model to propose six hypotheses to be tested using analysis tools Structural Equation Modeling (SEM) which is operated through a program AMOS 22.0. Based on the research of data processing SEM for full model has met the criteria of goodness of fit as follows, the value of chi-square = 132.455; probability = 0,071; RMSEA = 0,035; CMIN/DF = 1,204; GFI = 0,920; TLI = 0,982; CFI = 0,985; and a marginal criteria which is AGFI = 0,889. With the result, it can be said that this model is feasible to be used. The results showed that the service quality, perceived value, brand image can be improved by increasing customer satisfaction that affect the satisfactionÂ  as a determinant of success to increase customer loyalty